The Power of Teamwork: A Systematic Review of Multidisciplinary Team Management in Saudi Healthcare - Melebari, Safieah Hamza; Alanazi, Abdullah Mofareh; Mansouri, Eman Majid; Almutairi, Mohammed Abdullah; Almuqaytib, Mahmoud Yousef; Aljehani, Mohammad Eid; Alkahtani, Fahad Aboud Abdullah; Alqahtani, Faisal Abood Abdullah; Alharbi, Daleen Marzouq; Alanazi, Faiz; T. Alkhamash, Thanayan Awad; Alharbi, Amirah Senaitan; et al. (Journal of Ecohumanism, 2025)
Background: Multidisciplinary team (MDT) management has become one of the pillars of improving the delivery of healthcare, especially in severe patient care environments. The assimilation of MDT approaches has also been gradually appreciated in Saudi Arabia in terms of its capacity to increase clinical outcomes and patient satisfaction as well as support professional co-operation. Nonetheless, a methodical synthesis of the evidence, that is unique to Saudi healthcare settings is scanty. Purpose: The purpose of this study was to conduct a systematic review of the available literature on MDT management in Saudi healthcare to clarify some prevalent trends, topics, and issues and get insights to improve policy and practice in this regard. Method: A structured search of five big databases including PubMed, Scopus, Web of Science, CINAHL, and ScienceDirect within the last 5 years (2020-2024) was carried out. The PRISMA criteria were used to screen the studies, and quality assessment is realized using a standard, appraisal matrix. Thematic analysis was done on data synthesis to identify the core themes and sub-themes. Results: Study identified three significant themes: Communication efficiency, interprofessional cooperation, and patient-centered care, with ten studies found to conform to the inclusion criteria. Trends signaled the increasing integration of MDT approaches at the tertiary care and specialty units, with positive effects on the patient safety, the organization of treatment, and the satisfaction of the specialists and healthcare staff. Nonetheless, impediments, in the form of role ambiguity, resources limits and communication gaps, still remained. Conclusion: MDT management in Saudi healthcare proves to be very promising to enhance quality services and patient outcomes. Structural and communication barriers are necessary to address in order to maximize its benefits. Healthcare leaders and policymakers ought to focus on training, resources as well as standardized MDT protocols.